Pengaruh Pemahaman, Kesadaran, Tarif Pajak dan Pelayanan Perpajakan Usaha Mikro, Kecil dan Menengah di Kabupaten Karawang - Ajeng Resti Fauzi; Kholida Atiyatul Maula (Universitas Muhammadiyah Metro, 2020)
The purpose of this research is to know the influence of understanding, awareness, tax rates and taxation services of SMES taxpayer compliance. One of the efforts to help the economic development is in the presence of SMES in Indonesia. Development and development of the country will grow more if the state financing runs smoothly. One of the Government's efforts for the state financing to run smoothly is that the government needs a sufficient source of country for the development of the country that is being done by paying taxes. The population in this study is a SME which includes SMES champion in Karawang Regency period 2019, amounting to 58 MSMES. Data is collected by spreading the questionnaire to SMES The study used multiple linear analysis techniques. In partial testing the results showed that tax awareness and tariffs were influential for taxpayer compliance, while understanding and taxation services had no effect on the taxpayer's obligation. In the simultaneous testing of research results shows that understanding, awareness, tax rates and taxation services jointly affect taxpayer compliance.